Our dogs, ourselves : the story of a singular bond - Horowitz, Alexandra (Scribner, an imprint of Simon & Schuster, Inc., 2019)
"An eye-opening, informative, and wholly entertaining examination and celebration of the human-canine relationship." -- From book jacket flap.